Performance assessment of structural joints againstprogressive collapse in precast concrete structures - Akbari,S; Vollum,R; Izzuddin,B (fib International, 2025)
Adoption of precast concrete building systems is increasing, primarily due to reduced on-site construc-tion times and enhanced quality control. However, inherent discontinuity at the joints of precast struc-tures makes achievement of robustness challenging following sudden column loss. The paper uses acomponent-based NLFEA approach to investigate the effect of joint detailing on the robustness of apreviously tested full scale precast concrete building. The analysis shows that flexure was the principalload resisting mechanism following various sudden column removal scenarios. Detailed parametricinvestigations show that the global structural response is significantly influenced by choices made inthe modelling of the beam-column joints.